2007
DOI: 10.1111/j.1462-5822.2007.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic apoptotic pathways of gingival epithelial cells modulated by Porphyromonas gingivalis

Abstract: SummaryPorphyromonas gingivalis can inhibit chemically induced apoptosis in primary cultures of gingival epithelial cells through blocking activation of the effector caspase-3. The anti-apoptotic phenotype of P. gingivalis is conserved across strains and does not depend on the presence of fimbriae, as fimbriaedeficient mutants and a naturally occurring nonfimbriated strain were able to impede apoptosis. To dissect the survival pathways modulated by P. gingivalis, protein and gene expression of a number of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
201
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 201 publications
(213 citation statements)
references
References 69 publications
7
201
0
5
Order By: Relevance
“…The organism is intensely invasive, and high numbers of P. gingivalis cells rapidly accumulate in the perinuclear area of gingival epithelial cells (GECs) (2). Both host and internalized bacterial cells remain viable, and indeed, P. gingivalis can suppresses host cell apoptosis through modulation of intrinsic apoptotic pathways (44). In addition to the oral habitat, P. gingivalis can also spread systemically and locate in heart and gestational tissues (32,41), bone (67), and cerebrospinal fluid (25).…”
mentioning
confidence: 99%
“…The organism is intensely invasive, and high numbers of P. gingivalis cells rapidly accumulate in the perinuclear area of gingival epithelial cells (GECs) (2). Both host and internalized bacterial cells remain viable, and indeed, P. gingivalis can suppresses host cell apoptosis through modulation of intrinsic apoptotic pathways (44). In addition to the oral habitat, P. gingivalis can also spread systemically and locate in heart and gestational tissues (32,41), bone (67), and cerebrospinal fluid (25).…”
mentioning
confidence: 99%
“…Recent investigations have shown that P. gingivalis can accelerate the cell cycle of gingival epithelial cells (GECs) (18), reduce the apoptosis of GECs (19)(20)(21), and enhance the proliferation of immortalized human gingival epithelial cells (IGECs) (17). However, the effect of the individual stages of the host cell cycle on interactions with P. gingivalis has not been previously investigated.…”
mentioning
confidence: 99%
“…It was demonstrated that P. gingivalis transiently activates the JAK1/Stat3 pathways with Akt pathway modulation also being involved. These pathways up-regulate Survivin, at the mRNA level, and ultimately block activation of caspase-3 (122). Considering the many diverse signaling pathways engaged in apoptosis, it is not surprising that some bacteria inhibit or delay apoptosis while others induce it (230).…”
Section: P Gingivalis-induced Resistance To Apoptosismentioning
confidence: 99%